Performance Evaluation of Equity Mutual Funds in Indonesia - Irene Rini Demi Pangestuti; Sugeng Wahyudi; Robiyanto Robiyanto (University of Merdeka Malang, 2017)
Mutual funds considered an investment alternative for investors. One type of mutual fund that attracts many investors was the equity mutual funds. Equity mutual fund a type of mutual funds that most part of the investment consists of stocks in the capital market so the risk rate was higher than the other types of mutual funds. For its different characteristic, the measurement for equity funds performance did not be same with other types of mutual funds. As a stock portfolio, equity mutual funds can measure with portfolio measurement methods such as Sharpe Index, Treynor Ratio, Jensen Index, Adjusted Sharpe Index, Adjusted Jensen Index, and Sortino Ratio. This study was conducted by using all of those performance measurements as most research in Indonesia was conducted by using limited performance measurements (focusing on Sharpe Index, Treynor Ratio, and Jensen Index). This study aims to evaluate the performance of 42 equity mutual funds available in Indonesia by employing Sharpe Index, Treynor Ratio, Jensen Index, Adjusted Sharpe Index (ASI), Adjusted Jensen Index (AJI), and Sortino Ratio because most previous researches in Indonesian setting disregards ASI and AJI. In general, it was concluded that the SAM Indonesian Equity was the best-performing equity fund during the study period. It was further found that most equity mutual fund studied have been well diversified.DOI: https://doi.org/10.26905/jkdp.v21i4.1503